Automatic seismic-well tie based on cascaded matching optimization method - Li, Mengcheng; Huang, Xuri; Cao, Weiping; Wo, Yukai; Xu, Minghua; Ren, Mengyu; Lu, Shunkang (Frontiers in Earth Science, 2025)
Seismic-well tie, the alignment of synthetic traces with actual seismic traces at well locations, is a fundamental step in seismic interpretation, inversion, and reservoir prediction. This process involves multiple steps, including preprocessing well logs, calculating reflection coefficients, wavelet estimation, synthetic traces generation, and aligning synthetic traces with seismic data. This study focuses on the automated matching process, addressing its challenges and improving accuracy. Existing methods, such as correlation-based approaches, local similarity scan, and dynamic time warping, face limitations in handling time-varying shifts. To overcome these challenges, we propose the cascaded matching optimization method. This method decomposes the time shifts calculation into two steps: first, smooth time shifts are determined using local similarity scan while preserving waveform characteristics to perform an initial correction; second, the corrected synthetic trace is refined to account for residual shifts. Tests using synthetic and field data demonstrate that this method achieves accurate automatic seismic-well tie while preserving waveform fidelity.